1997
DOI: 10.1111/j.1740-8261.1997.tb01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Renal Size in Dogs With Acute Allograft Rejection

Abstract: The purpose of this study was to determine the best method to ultrasonographically monitor renal size changes associated with acute allograft rejection in dogs. Qualitative changes in renal cortical and medullary echogenicity were also evaluated, although this was not a major focus of the study. Four unrelated, mixed-breed dogs underwent bilateral nephrectomies and heterotopic renal allograft transplantation. Ultrasound examinations of transplanted kidneys were initiated at 3 days after surgery and continued a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…For this reason, although CT-GFR was calculated, statistical comparison was not made with the group 1 dogs. Renomegaly, which may be as great as a 103% increase in volume following renal allograft, is caused by a combination of compensatory hypertrophy, acute tubular necrosis, acute/chronic rejection and glomerulonephritis (25,26). In the study herein, tubular degeneration/dilatation was seen and there may have been a degree of hypertrophy to explain the renomegaly, but neither of these cause an increase in interstitial space.…”
Section: Patlak Plot Ct-gfr For Kidney Transplant In Dogsmentioning
confidence: 59%
“…For this reason, although CT-GFR was calculated, statistical comparison was not made with the group 1 dogs. Renomegaly, which may be as great as a 103% increase in volume following renal allograft, is caused by a combination of compensatory hypertrophy, acute tubular necrosis, acute/chronic rejection and glomerulonephritis (25,26). In the study herein, tubular degeneration/dilatation was seen and there may have been a degree of hypertrophy to explain the renomegaly, but neither of these cause an increase in interstitial space.…”
Section: Patlak Plot Ct-gfr For Kidney Transplant In Dogsmentioning
confidence: 59%
“…Subcapsular or perirenal fluid may result from urine leakage, 121 hemorrhage, 128 abscess, 71,91,117,120,129,130,134 acute renal failure, 121 ureteral obstruction, 121 toxicity 76,121 (e.g., ethylene glycol), leptospirosis, 77,121 transplant rejection, 135 or renal neoplasia (Figure 16-26, A). With smaller amounts of fluid, it may be difficult to determine if the fluid is subcapsular or perirenal and therefore they are considered together here.…”
Section: Subcapsular Fluid or Thickening And Perirenal Fluidmentioning
confidence: 99%
“…As kidney volume is better than linear measurements to assess changes in kidney size, several methods for the ultrasonographic evaluation of kidney volume have been reported [3,4,5, 12, 17, 23, 24]. However, they tend to underestimate kidney volume and are complex for practical use [1, 3,4,5, 12, 17, 18, 23, 24, 31]. Previous studies have shown that kidney length is also well correlated with actual kidney size [3, 5, 6, 13, 15, 24, 25, 31].…”
mentioning
confidence: 99%